POSSIBILITIES OF THE “QUEST” TECHNOLOGY IN TEACHING FOREIGN LANGUAGES - Ergasheva, Jasmina Shuxratovna; Ziyadullayeva , Aziza Akmalovna (GOLDEN BRAIN, 2024)
This article gives information about the possibility of using the "Quest" pedagogical technology in secondary education, gives its detailed characteristics and provides a description of the quest conducted in the 9th grade of secondary school in English classes and after school hours. It is noted that this technology is quite applicable in teaching foreign languages at school, since it is aimed at solving a set of tasks that local education is facing currently.